ESG IMPACT ON POST M&A COMPANY VALUE IN SOUTHEAST ASIA - Mutiara Putri Sihombing; Imo Gandakusuma (Jurnal Aplikasi Akuntansi, 2023)
This study examines the influence of ESG scores on the financial performance of post-M&A acquirer companies. The instrumental stakeholder theory views that high ESG performance could earn support from stakeholders for post-M&A synergy creation and financial performance. Previous studies have shown different results regarding the effect of ESG scores on a company's financial performance, thus indicating the ongoing relevance of this topic. Drawing on a sample of 135 M&A transactions in Southeast Asia, this study presents novel evidence of the financial benefits of ESG performance for acquiring companies. The findings of this research reveal a positive correlation between the ESG scores and post-M&A performance, thereby supporting prior research that aligns with instrumental stakeholder theory.